Corporate Legal Liability for Corruption in the Private Sector - Idrus Salam; Satria Unggul Wicaksana Prakasa (Indonesian Journal of Law and Society, 2021)
Corruption in the private sector has been an emerging issue in Indonesia, regarded to become a serious problem to the rule of law. In this case, the problem is the difficulty in tracking down perpetrators of corruption in the private sector since legal accountability does not pay serious attention. For example, the Rolls Royce case involved many jurisdictions in Indonesia that experienced obstacles due to limited authority and low commitment from the country. This study aimed to examine how private sector corruption is linked to legitimizing bribery by foreigners by answering the following questions: what is the legal liability of corporations as perpetrators of corruption in the private sector? What are the legal mechanisms in Indonesia for understanding private sector corruption? In this study, the socio-legal method was used to analyze corruption as a national and international crime to respond to the raised legal issues. The socio-legal method is a legal research method that can do more than regulate the law. The results indicated that the pattern of corruption in the private sector for officials could result in corrupt policies. Furthermore, for the private sector, it can lead to unfair business competition. Therefore, it must be handled immediately so corruption cases in the private sector cannot continue to occur, causing harm to the public and indirectly affecting the country. KEYWORDS: Corruption, Criminal Liability, Private Sector.